JARINGAN SARAF TIRUAN DALAM MEMPREDIKSI SUKUK NEGARA RITEL BERDASARKAN KELOMPOK PROFESI DENGAN BACKPROPOGATION DALAM MENDORONG LAJU PERTUMBUHAN EKONOMI - Agus Perdana Windarto; Solikhun Solikhun; Handrizal Handrizal; M Fauzan (Lambung Mangkurat University, 2017)
State Retail Sukuk is a Sharia Securities issued and its sale is regulated by the State, namely the Ministry of Finance (Depkeu). Where the government will choose the seller agent and consulting retail sukuk law. Selling agents must be obliged to have a commitment to the government in the development of the sukuk market and experience in selling Islamic financial products. The publication of this instrument is likened to a